On Some Aspects of the Lilleoru Community - Kaidi Tamm (Journal of Ethnology and Folkloristics)
This paper explores the raison d’être of the only proper Estonian ecovillage, Lilleoru. Exceptional in the Estonian context, this relatively small and young community is a member of three established international networks uniting similar communities. Based on fieldwork and ethnographic interviews, the present article describes some focal aspects of the community and investigates how Lilleoru functions as a community. After a brief overview of the formation of the community, the following questions are touched upon: what is its significance for its members, how are they differentiated from other similar groups, what creates coherence among its members, how is the community managed, what are the everyday practices and how does it fit into the global context. As a result of the study it might be said that although from the outside Lilleoru is mainly seen as an ecovillage, from inside being an awareness training centre is central. The ecological lifestyle is regarded as a side result of a conscious lifestyle.